Biochemical markers for screening of ovarian cancer - Tkaczuk-Włach, Joanna; Sobstyl, Małgorzata; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2013)
Ovarian cancer has the highest mortality rate among gynecological cancer. Despite the development of new treatments five-year survival rates fall below 20%. This article is a review of the knowledge of the current markers and potential screening tests and their role in early detection of ovarian cancer.